(untitled) - Robert F Chandler (Boulder, Colorado, 1979)
The book consists of 8 chapters. Chapter 1 conveys the importance of rice as a world food crop and describes some of its unique qualities. In chapter 2 and 6, an effort is made to set forth the current stage of rice research and technology and to identify some of the more promising research projects that merit continuing attention. Chapter 3 and 4 treat portharvest problems, including way of handling surplus rice production. Chapter 5 describes in some detail for national rice production efforts that achieved positive results. Chapter 7 contains a discussion of the more important elements of a successful rice production program. Chapter 8 is devoted to the subject of putting the elements discussed in chapter 7 into a workable scheme. The appendix describes the more important international agencies offering technical and financial assistance for agricultural development programs. Following the appendix are an annotated bibliography, arranged in the order of chaptewr content, and a glossary of terms
Keywords: agriculture and state,farm management,rice,rice - tropics